EFFICIENCY OF PLANTING CALCIUM IONS FROM DILUTE AQUEOUS SOLUTIONS IN THE FORM OF PHOSPHATES - GORDIENKO, Katerina; RADOVENCHYK, Yaroslav; KRYSENKO, Tamara; RADOVENCHYK, Vyacheslav (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The specifics of calcium phosphate formation process during diluted aqueous solutions softening for home or office were researched. Studies have shown that, unlike calcium carbonate, effective precipitation of calcium ions with phosphate is possible even at doses less than stoichiometric. The ratio between concentrations of phosphate ions and calcium ions K = [PO43-, mg-eq] / [Ca2+, mg-eq] is a determining factor. Already at K = 0.5 there is a decrease in the content of calcium ions by more than half. In stoichiometry (K = 1), the residual concentrations of calcium ions in the treated water fall below 1 mg-eq/dm3. At K > 1.5, the content of calcium ions in the treated water stabilizes at the level of 0.2 – 0.1 mg-eq/dm3. Water temperature does not significantly affect the deposition of calcium ions with phosphates. A noticeable decrease in efficiency is recorded only at a temperature of 5 ° C. But even in this case, this decrease is 0.1 – 1.5 mg-eq/dm3, which is quite acceptable for living conditions, since it provides soft and very soft water. The reaction between calcium ions and phosphates is quite complete in the first minutes of contact. The settling of mixed solutions for an hour showed that the reaction of the formation of a solid phase takes place at the time of draining the solutions and over time the residual hardness of the water practically does not change. From the point of view of softening efficiency, phosphate is quite suitable as a reagent for removing calcium ions from hard natural waters. An important aspect of the softening technology is the separation of the precipitate formed from the treated water. To do this, it is necessary to determine the conditions for the formation of a crystalline, most compact and formed precipitate. The clarification of the hard water sample treated with sodium phosphate showed that there was no significant difference in deposition at different initial pH values.